La compensación bancaria y el derecho constitucional a la remuneración - Nuñez Leyva, Yrma Stephani (2016)
The purpose of this investigation is to determine if banking compensation of an employee’s salary affects the constitutional right to have a remuneration and its alimentary character, because of the multiple resolutions issued by Indecopi in the last years. The investigator has used deductive, dogmatic and exegetic methods, obtaining as results that Indecopi is not respecting the constitutional right of having a salary, as far as in recent decisions it has analyzed how the fact of prohibit the possibility of banking compensation generates a negative effect in credit market, in spite that making a systematic interpretation even based on legal disposition contained in our normative, that specifies that compensation of remuneration is forbidden as it is established in the 648 article of the Civil Procedure Code, also setting aside the alimentary character of remuneration, allowing in this way that conventional compensation as a possibility. In conclusion, this investigation concludes that banking compensation infringe the constitutional right of a salary and it’s alimentary character, putting on risk even the employee’s life and it’s family